2005
DOI: 10.1055/s-2005-837517
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Morbidity in Women with Undiagnosed Gestational Diabetes in Northern Thuringia in Germany

Abstract: More than one third of the mothers having born one or more macrosomic infants had an impairment of glucose metabolism immediately after birth. The elevated prevalence of preeclampsia in this group confirms the relationship of hypertension and impaired glucose metabolism during pregnancy. The detection of hyperinsulinaemia, postnatal hypoglycaemia, elevated prevalence of neonatal jaundice with need of further therapy and diabetic fetopathy in macrosomic infants of mothers, whose metabolism was not monitored dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Macrosomia is associated with pregnancies complicated by poorly controlled diabetes (Boulet, Alexander, Salihu, & Pass, 2003; Hunger‐Danthe et al, 2005), and is defined as birth weight above 4000 g or more than the 90th percentile for gestational age (Battaglia & Lubchenco, 1967). Macrosomia, itself, has been associated with childhood obesity (Vohr & McGarvey, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Macrosomia is associated with pregnancies complicated by poorly controlled diabetes (Boulet, Alexander, Salihu, & Pass, 2003; Hunger‐Danthe et al, 2005), and is defined as birth weight above 4000 g or more than the 90th percentile for gestational age (Battaglia & Lubchenco, 1967). Macrosomia, itself, has been associated with childhood obesity (Vohr & McGarvey, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Untreated GDM carries significant risks for perinatal and maternal morbidity [1,5]. Several studies showed the efficacy of early GDM management, based on dietary advice, blood glucose monitoring, and insulin therapy as needed [5,6], thereby reinforcing the necessity of GDM screening [7]. Three major screening tests are used [8]: (i) the classical diagnostic test proposes a 100‐g oral glucose tolerance test (OGTT) given in a fasting state and measurement of plasma glucose at 0, 1, 2 and 3 hours; (ii) the glucose‐challenge test proposed by O’Sullivan and Mahan in 1964 [9] is based on a 50‐g glucose load with measurement of the glucose level 1 hour later; it should be confirmed by a 100‐g OGTT; and (iii) the World Health Organization (WHO) has recommended a 75‐g OGTT in the fasting state followed by a plasma glucose determination 2 hours later [10].…”
Section: Introductionmentioning
confidence: 99%
“…По прогнозам ВОЗ, к 2025 г. ко-личество больных СД в мире увеличится в два раза и достигнет 333 млн человек [2].…”
Section: Introductionunclassified